Pengembangan Aplikasi Kamus Bahasa Isyarat Indonesia (Bisindo) dengan Mengintegrasikan Cloud Video Berbasis Android - Nuryazid, Nuryazid; Mulwinda, Anggraini (Jurusan Teknik Elektro Universitas Negeri Semarang, 2017)
Sign language learning application to be able to help its users in order to learn sign language easily namely a sign language dictionary application can display video in it, is needed these day. The popularity of using android operating system in the general society makes the development of Indonesian sign language dictionary application based on android. This application development is using the software development waterfall model that consists of a stage needs analyze includes an analysis of user needs, preparation tools and the materials development, system design in the form of use case diagrams, activity diagram, sequence diagram, as well as interface design, coding by using the Java programming language, to the testing of products include the black-box test, experts test, and users test. The result of this application development is a dictionary application of sign language that can display a video of Indonesia language sign movement. Black-box testing result showed the application was already running in accordance with the design that has been created. Testing applications by material and media experts indicated that this application has a very good quality. Also for the application user testing results conducted 22 people studied the sign language, they indicated that the application has a very good functional qualities. Based on the results of these tests, then it can be inferred that Indonesian sign language dictionary application development can be used as a learning tool for helping Indonesian people to study about the sign language.